Comprehensive Analysis of Radiological Innovations, Safety Protocols, and Clinical Applications in Diagnostic Imaging and Collaboration Between X-Ray Technicians, Nurses, and Clinicians - Alsubhi, Sultan Khalid Mohammed; Aloufi, Meshal Ali Turyes; Alharthi, Abdulaziz Khalaf Zayed; Alzhrani, Hussain Ahmed Turaikhm; Althagafi, Mohammed Atiah Awadh; Alharthi, Faisal Rezkallah A; Alshehri, Majed Mohammed; Aljomuai, Abdulmajeed Eidah (Journal of Ecohumanism, 2024)
Advancements in radiology have enhanced the method of diagnosis by ensuring highly accurate imaging results fruitful for patients. Huge developments like digital radiography, CT, MRI, and AI have improved the quality and speed of imaging services. However, remaining safety measures and effective collaboration between X-ray technicians, nurses, and clinicians to get better outcomes for a patient and reduce risks of potential radiation exposure are still important. This paper aims to present a synthesis of literary findings on recent advances in radiological examination techniques, their uses, measures to be taken to prevent harm to patients and/or staff involved in the examinations by radiation, and the required teamwork and collaboration for effective healthcare services to be rendered to patients. The study suggests that the progressive development of technology could only be met with sound safety features and improved collaboration of interdisciplinary team members to attain ideal clinical utilization.